La intervención de niños niñas y adolescentes En la comisión de hechos delictivos como Resultado de su participación en bandas Dedicadas a actividades delictivas debe ser Tipificada y penalizada como delito de Corrupción de menores - Morales Torres, Julio Emilio (2016)
Undoubtedly juvenile delinquency is one of the most serious social phenomena in our societies and internationally is one of the most investigated criminological problems from the last century, as the manifestations of social behavior that draws negative attention can be seen, usually better among young people in the adult population. I consider it important to address juvenile delinquency today morning as a possible adult crime; Therefore this research is of great interest because I take into account the various factors that comprise the problem, analyzing the legal measures that are used for the treatment and rehabilitation of young offenders, helping to do definitions and terms concerning crime youth and as the possible profile and factors favoring their behavior, the current proposal to reform the penal age in the country, with the justification for this. Ecuador at the present time is going through a very hard and cruel social reality, affecting in different ways, one of which is the increasing juvenile crime, it would be very easy to meet increasing rates of crime, however, I do not want to play therefore figures do not reflect the social reality by passing these people daily televised and written media realize murders, assaults, robberies, and drug sales in which children and adolescents are. Juvenile delinquency is located in Ecuador, within a social context characterized by groups of children and adolescents placed in misery and poverty levels, unemployment, drug trafficking, urban concentration, low education or illiteracy, sexual abuse and family breakdown, to these social groups have been denied all human, such as the right to life, health, education, housing, finally, the right to development rights. In this context, we must add that today's society is characterized by a weakening of traditional support systems for the development of childhood and adolescence, so I would mention that some who, with the social changes that are been made to respond effectively to the development of children and adolescents, first I should mention to the family, the media, especially television, have abolished the hierarchy and hegemony that the family had as forming habits Social addition, the incorporation of women into the labor system, by necessity or development opportunities, and other changes in family structure, and the general absence of the father, rethinking the relationship of the child and the young, the obligation of children to study compulsorily, School, meanwhile, is characterized by a strong emphasis academista and fierce competitiveness, erasing the sense of community and promote the comprehensive development of young people. In addition, assistance systems and Recreation, as alternative supports, we are minimal and insufficient to satisfy the needs of the youth population. this context juvenile delinquency is the result of a combination of various risk factors and social response, it occurs in every society, where the negative values of violence, aggression, fierce competition, consumption, supreme values of society are imposed such as tolerance, solidarity and justice. In Ecuador has been historically characterized as recipient of European conceptions of law, it has evolved into a legal world that often does not correspond to reality, a right that remains estranged from the existing objectivity, back to reality cultural and social, unknown and ignored by vast segments of the population, unfortunately we must recognize that the Ecuadorian legal tradition rests on a glaring dichotomy between discourse and practice, on the one hand presents a liberal, democratic and guarantor law, which is quickly distorted and distorted reality for the real factors of power, juvenile criminal law is no exception in this divorce between the theoretical and the practical. In this regard we must be clear that the gangs are organized in study centers, groups that supposedly control the others by imposing its strength, logically with the external address which will gradually recruited to perform different activities are formed, They initiated by the theft of belongings of their peers, in the sale of narcotics and psychotropic substances, which are the first steps in school crime, thus they are perfected to when they meet adulthood are real criminals , we can say that our country especially in the most populated cities juvenile delinquency is uncontrollable somewhat inefficient police to control this social evil.